2008
DOI: 10.1309/jvb8qfqnw5hbn7uj
|View full text |Cite
|
Sign up to set email alerts
|

False-Positive Sentinel Lymph Nodes in Breast Cancer Patients Caused by Benign Glandular Inclusions

Abstract: We report 3 cases of sentinel lymph nodes (SLNs) containing benign glandular inclusions (BGIs) in patients with breast carcinoma that were initially misdiagnosed as metastatic carcinoma. The first case had an SLN with glandular elements adjacent to a squamous inclusion cyst, the second had an SLN with a single complex gland showing apocrine features, and the third had 2 SLNs, each containing rare glands lined by bland columnar cells and surrounded by thin, fibrous bands. All glandular elements were distinctly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 10 publications
(15 reference statements)
0
20
0
Order By: Relevance
“…37 Because the OSNA assay is designed not to recognize tumor cells corresponding to ITCs, this is unlikely to be a source of error in the test. However, benign intranodal epithelial inclusions, such as heterotopic mammary glands, benign glandular inclusions, or benign Mullerian inclusions, are inevitable for the false-positive diagnoses, [38][39][40][41] although their presence is a rare event in axillary lymph nodes. Clinical trials comparing OSNA assay and histopathological examination have demonstrated a high specificity (96% to 97%) after investigating discordant cases.…”
Section: Discussionmentioning
confidence: 99%
“…37 Because the OSNA assay is designed not to recognize tumor cells corresponding to ITCs, this is unlikely to be a source of error in the test. However, benign intranodal epithelial inclusions, such as heterotopic mammary glands, benign glandular inclusions, or benign Mullerian inclusions, are inevitable for the false-positive diagnoses, [38][39][40][41] although their presence is a rare event in axillary lymph nodes. Clinical trials comparing OSNA assay and histopathological examination have demonstrated a high specificity (96% to 97%) after investigating discordant cases.…”
Section: Discussionmentioning
confidence: 99%
“…This is described in association with intraoperative techniques for assessment of SLNs, including frozen section examination [13,14], but it also a potential problem with intraoperative touch imprint cytology and qRT-PCR (quantitative reverse transcriptase-polymerase chain reaction). However, this remains an issue even in a formalin-fixed, paraffin-embedded material; reports of benign inclusions misdiagnosed as metastatic disease are recorded [4,5,14]. Although malignant change in such inclusions is exceptionally rare, this adds a further level of difficulty to reaching the correct diagnosis when epithelial inclusions are present.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry was performed on lymph nodes (all levels) of ten male and ten female patients, chosen at random prior to the examination of H&E sections. For that purpose, we applied a pan-cytokeratin antibody (clone MNF116, DAKO, Carpinteria, CA; dilution 1:100), which covers a wide spectrum of cytokeratins (cytokeratins 5,6,8,17,19).…”
Section: Methodsmentioning
confidence: 99%
“…Not infrequently, salivary gland and thyroid fragments are found in cervical lymph nodes and melanocytic nevus cells in axillary and inguinal nodes [4]. Anatomical pathologists occasionally encounter ectopic breast tissue, embryologic remnants of the milk line, in the axillary fat as well as in the capsule and parenchyma of axillary lymph nodes [5][6][7][8][9]. It stands to reason that these ectopic epithelial elements will be recognized by intraoperative PCR and hence interpreted as metastasis.…”
mentioning
confidence: 99%